Membrane activity of a supramolecular peptide-based chemotherapeutic enhancer. Issue 9 (11th July 2016) - Xu, Dawei; Jiang, Linhai; DeRidder, Louis; Elmore, Brendan; Bukhari, Maurish; Wei, Qiang; Samways, Damien S. K.; Dong, He
Abstract : This work explored the membrane activity of filamentous supramolecular peptides and their great potential as a supramolecular peptide-based chemotherapeutic enhancer. Abstract : Self-assembly of de novo designed multidomain peptides (MDPs) resulted in functional membrane-active supramolecular nanofibers. The membrane activity was analyzed through fluorescence membrane localization and patch-clamp electrophysiology yielding important information that can be used for the development of a new type of supramolecular peptide-based chemotherapeutic enhancer.